Interest of Single Hair Analysis to Document Drug Exposure: Literature Review and a Case Report Involving Zuclopenthixol - Allibe, Nathalie; Kintz, Pascal; Faure, Amandine; Paysant, Francois; Michard-Lenoir, Anne-Pascale; Stanke-Labesque, Francoise; Scolan, Virginie; Eysseric-Guerin, Helene (Current Pharmaceutical Design, 2017)
The analysis of hair to detect drugs and drugs of abuse is performed in various contexts, including child protection cases, abstinence control programs, and workplace drug testing. This alternative matrix offers several advantages, such as a large detection window (months) and non-invasive collection. Segmental analysis of multiple hair strands for drugs and metabolites has been widely reported in the literature over the past three decades, whereas a review of the literature showed that there are only 26 articles that report the analysis of a single hair. They focus on two approaches: mass spectrometry imaging techniques, which improve the resolution of dating an intoxication or conventional methods, such as gas chromatography mass spectrometry and liquid chromatography tandem mass spectrometry (LC-MS/MS). Improved sensitivity of LC-MS/MS techniques allows the evaluation of drug content in segments of a single hair. However, the units used to express the results vary, and depend on the authors. Following a review of the literature, we present a case that illustrates drug analyses both in a strand of hair and a single hair. In this case of exposure of a child to zuclopenthixol (ZPT), the analysis of ZPT in a single segmented hair by LC-MS/MS strengthened the presumption of a single administration.
Keywords: hair analysis